Alloplasty for Open Tracheal Defects - Bakhromova Odina Alisherovna; Eshonkhodjaev O. D.; Khayaliev R. Y.; Tursunov N. T.; Rikhsiev Z. G. (Scholars Digest Publishing, 2024)
This article studies the use of alloplasty in open tracheal defects. Today, early innovative diagnosis and prevention of tracheal defects is one of the most urgent problems in medicine.
Keywords: trachea, defects, methods of plasty.